New culture in a new world : the May Fourth movement and the Chinese diaspora in Singapore, 1919-1932 - Kenley, David L., 1968- (East Asia (New York, N.Y.), 2003)
Analyzes the New Culture Movement from a diaspora perspective, namely that of the overseas Chinese in Singapore who had to imagine themselves as part of the Chinese nation before they could fully participate in the movement.